Regional anesthesia in Canadian emergency departments: Emergency physician practices, perspectives, and barriers to use. Issue 4 (July 2020) - Wiercigroch, David; Ben-Yakov, Maxim; Porplycia, Danielle; Friedman, Steven Marc
ABSTRACT: Objectives: Regional anesthesia has many applications in the emergency department (ED). It has been shown to reduce general anesthetic dose, requirement for post-procedural opioids, and recovery time. We sought to characterize the use of regional anesthesia by Canadian emergency physicians, including practices, perspectives and barriers to use in the ED. Methods: A cross-sectional survey was administered to members of the Canadian Association of Emergency Physicians (CAEP), consisting of sixteen multiple choice and numerical response questions. Responses were summarized descriptively as percentages and as the median and inter quartile range (IQR) for quantitative variables. Results: The survey was completed by 149/1144 staff emergency physicians, with a response rate of 13%. Respondents used regional anesthesia a median of 2 (IQR 0–4) times in the past ten shifts. The most broadly used applications were soft tissue repair (84.5% of respondents, n = 126), fracture pain management (79.2%, n = 118) and orthopedic reduction (72.5%, n = 108). Respondents agreed that regional anesthesia is safe to use in the ED (98.7%) and were interested in using it more frequently (78.5%). Almost all (98.0%) respondents had point of care ultrasound available, however less than half (49.0%) felt comfortable using it for RA. Respondents indicated that they required more training (76.5%), a departmental protocol (47.0%), and nursing assistance (30.2%) to increase their use of RA. Conclusion: Canadian emergency physicians use regional anesthesia infrequently but express an interest in expanding their use. While equipment is available, additional training, protocols, and increased support from nursing staff are modifiable factors that could facilitate uptake.